Synthesis of Clausena Alkaloids Using Unique Ring Expansion of Dihydroisoquinolines and Their Cholinesterase Inhibitory Activity - Worayuthakarn, Rattana; Ngernnak, Chuleeporn; Ruchirawat, Somsak; Chainok, Kittipong; Wannarit, Nanthawat; Thasana, Nopporn (Synthesis, 2023)
A facile and direct synthetic entry to the carbon skeleton of Clausena alkaloids, the benzo[d]azocin-4-one, is reported featuring the ring expansion of 1-phenyldihydroisoquinoline derivatives initially triggered by oxazolone under environmentally benign conditions in a one-pot procedure. Functionalization of the eight-membered lactam framework provided a set of Clausena alkaloid derivatives. Some derivatives show a promising inhibition toward acetylcholinesterase and a better selectivity index than the previously used Alzheimer’s disease (AD) drug, tacrine, and the currently used AD drug, galantamine.
Keywords: Clausena alkaloids; ζ-clausenamides; balasubramides; benzo[d]azocinones; eight-membered lactams; ring expansion